An Inductive-Contextual Arabic Grammar Using Historical Texts: A Case Study in a Modern Islamic Boarding School - Fikri, Ahmad; Harisah; Munir, Moh.; Fadhlan, Muhammad (Institut Agama Islam Negeri Curup, 2025)
Arabic grammar is essential for accessing both classical and modern texts; however, its instruction in Islamic boarding schools (pesantren) has often remained deductive, theoretical, memorization-based, and decontextualized. This gap makes it difficult for students to apply grammatical rules effectively in real comprehension tasks. This study investigates how historical narrative texts can support a more inductive and contextual pedagogy. Conducted at Darul Qiyam Modern Islamic Boarding School, Kerinci, Indonesia, the research employed a qualitative case study design involving in-depth interviews, classroom observations, and document analysis with four Arabic grammar teachers. The findings identified four main strategies: (1) Direct Explanatory Scaffolding, offering initial orientation through brief explanation and modeling; (2) Pattern Repetition, reinforcing guided noticing and output variation using authentic text patterns; (3) Inductive-Contextual Exploration, where learners infered rules through meaning-driven analysis of historical discourse; and (4) Inductive-Collaborative-Constructivist Practice, fostering group dialogue, peer explanation, and reflective scaffolding. These strategies aligned with pedagogical parameters such as guided noticing, form–meaning mapping, structural variation, social mediation, and visual scaffolding. The approaches enhanced grammatical sensitivity, reduced reliance on rote memorization, and promoted learner autonomy. However, negative cases revealed that some students remained dependent on memorized rules or struggled with complex patterns. The study concludes that inductive-contextual strategies supported by historical texts can meaningfully transform grammar instruction in Islamic boarding schools. Recommendations include integrating such texts into curricula, providing teacher training in constructivist pedagogy, and conducting further research on learner differences and digital scaffolding.